2018
DOI: 10.1002/cb.1723
|View full text |Cite
|
Sign up to set email alerts
|

Showing to friends or strangers? Relationship orientation influences the effect of social exclusion on conspicuous consumption

Abstract: Previous research has shown that social exclusion can lead individuals to engage in conspicuous consumption, but these studies did not focus on the relationship between the excluder and the excluded, that is, whether they were friends or strangers. The present research aims to address this gap by taking relationship orientation as a boundary condition between social exclusion and conspicuous consumption. The results of Experiment 1 demonstrate that individuals who are communal relationship oriented (e.g., frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…The current research contributes to the literature on social exclusion effects in the domain of consumption. Recent work has found that interpersonal exclusion can influence consumers' product preferences, such as increasing individuals' interest in nostalgic products (Loveland, Smeesters, & Mandel, 2010), preferences for distinctive products (Wan, Xu, & Ding, 2013), or rates of conspicuous consumption (Lee & Shrum, 2012; Liang, He, Chang, Dong, & Zhu, 2018). Our findings enrich this line of research by examining consumers' reactions when the source of the exclusion is a luxury brand.…”
Section: Discussionmentioning
confidence: 99%
“…The current research contributes to the literature on social exclusion effects in the domain of consumption. Recent work has found that interpersonal exclusion can influence consumers' product preferences, such as increasing individuals' interest in nostalgic products (Loveland, Smeesters, & Mandel, 2010), preferences for distinctive products (Wan, Xu, & Ding, 2013), or rates of conspicuous consumption (Lee & Shrum, 2012; Liang, He, Chang, Dong, & Zhu, 2018). Our findings enrich this line of research by examining consumers' reactions when the source of the exclusion is a luxury brand.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, extant literature shows the negative relationship between self-esteem and conspicuous consumption. When people are socially excluded from the close relationship (e.g., friends), they experience weakened self-esteem, which in turn makes them prefer conspicuous consumption ( Liang et al., 2018 ). Those with low self-esteem prefer brands such as luxury brands that can signal high social status in order to ensure their group inclusion in the future even when they experience a sense of belonging ( Dommer et al., 2013 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Communal-oriented individuals will prefer to consume conspicuous products when they experience social exclusion rather than social inclusion and that this behavior is driven by self-esteem evoked from comparing differences of self-orientation (Liang, He, Chang, Dong & Zhu, 2018). Upward social comparison, as opposed to downward comparison, increased preference for the conspicuous consumption (Zhang, Xu, Zhao & Yu, 2018).…”
Section: R M B Rmentioning
confidence: 99%